The Use of Map Media: A Study of Spatial Thinking Skills - Mawarni, Lisa; Ahyuni, Ahyuni (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2025)
The Use Of Map Media: A Study Of Spatial Thinking Skills. This study aims to analyze the effectiveness of using map media in improving students' spatial thinking skills in biosphere phase E (class X) material at SMAN 1 North Kampar. Spatial thinking is very important in science education to understand spatial relationships in ecosystems, but biosphere learning faces complex challenges related to the interaction of organisms and their environment. Therefore, the use of map media, both digital and printed, is integrated in ecosystem analysis and prediction of environmental change to improve students' understanding. This study used a quantitative approach with a quasi-experimental method and Non-Equivalent Group Design. The research sample consisted of 30 students of class X3 as the experimental group and 30 students of class X1 as the control group. The intervention was conducted for two weeks in the odd semester. Data analysis using Independent Sample T-Test showed a significance value (sig = 0.001 <0.05), which means there is a significant difference between the two groups. N-Gain results showed that the experimental class had high effectiveness in spatial thinking (76.68%), while the control class was less effective (55.58%). These results show that map media can be used as an effective learning tool to improve students' spatial thinking skills. Teachers can utilize interactive or digital maps in ecology learning to clarify the concept of space and improve students' understanding of the biosphere.